Особливості внутрішньої форми фразеологізмів із лексемами на позначення вогню - Бечко, Я. (Лексикографічний бюлетень, 2011)
The author analyses, with reference to the Ukrainian, English and German languages,
the peculiarities of the inner form of idioms with nouns denoting fire. Proceeding
from relationship between idiomatic meanings this noun acquires within idiom-internal
context and the character of idiom’s inner form, she finds out that some of these derivative
meanings (eg, „source of negative destructive influence” or „positive constructive
influence”) tend to correlate with inner forms denoting, as their literal sense, a real-life
situation (such as adding fuel to fire, cooking on fire etc), while others (such as „source
of intensifying influence on other person’s activity” or „some mental characteristics as
well as their facial expression”) are conveyed by inner forms depicting them in terms
of purely poetic imagery (presumably mythological in its origins) identifying emotions
with fire. She also considers such features of inner form as transparency, universality,
metaphoric/metonymic nature and also its source.